The functional form of the demand for euro area M1 - Livio Stracca (European Central Bank (ECB), 2001)
A remarkable development seen in recent years is the pronounced decline in euro area M1 velocity vis–vis a moderate decline in short-term interest rates, which represent the most natural opportunity cost for M1, suggesting an increase in the interest rate elasticity of M1 demand. In fact, estimating a theoretically plausible and stable demand function for M1 in the euro area is possible, if a functional form of money demand allowing for an interest rate elasticity decreasing in size with the level of the interest rate is imposed. This finding would apparently suggest that the decline in inflation and nominal interest rates in Europe experienced in the run-up to the euro should have 'naturally' brought about an increased degree of preference for liquidity without any fundamental change in agents' preferences. To test the validity of this conclusion, a time-varying parameters model is estimated through Kalman filter on the level of real M1, which is able to test simultaneously the stability of the parameters and the functional form of the demand for euro area M1. In this case, results clearly suggest the double log function to be very close to the true 'deep' functional form of M1 demand in the euro area, consistent with the findings of Chadha, Haldane and Janssen (1998) for the United Kingdom and of Lucas (2000) for the United States. At the same time, there is evidence of an increased interest rate elasticity in M1 demand in the most recent years, presumably associated with the transition to the new environment prevailing from the start of Stage Three of EMU
Keywords: E41; E52; 330